An Intra-firm perspective on wage profiles and employment of older workers with special reference to human capital and deferred compensation - Christian Pfeifer (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2009)
Human capital and deferred compensation might explain why firms employ but do not hire older workers. Adjustments of wage-tenure profiles for older new entrants are explored in the context of deferred compensation. From an equity theory perspective, such adjustments might lead to adverse incentive effects so that firms prefer to hire rather homogenous workers in terms of entry age. A personnel data set is analyzed which reveals that at least for white-collar workers entry age has a positive effect on entry wages and wage-tenure profiles are adjusted according to entry age.
Keywords: J14; J24; J31; J33; M51; M52; 330; Deferred compensation; human capital; internal labor markets; older workers; wages